2020
DOI: 10.1016/j.ijscr.2020.06.079
|View full text |Cite
|
Sign up to set email alerts
|

Surgical debridement as a treatment strategy for cervicofacial actinomycosis—Literature review and case report

Abstract: Highlights Antibiotic therapy and surgical debridement as a form of treatment of actinomycosis. Actinomycosis does not respond well antibiotic therapy before curettage. Debridement proved to be important for the reduction of antibiotic therapy time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
2
0
2
Order By: Relevance
“…However, an additional review of the literature without excluding prosthesis revealed more cases, where Actinomyces species caused prosthetic joint infection [ 19 ]. Drug resistance is not considered a problem in actinomycosis, therefore penicillin G or amoxicillin are considered first-line drugs for the treatment of actinomycosis together with surgical debridement of abscesses [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, an additional review of the literature without excluding prosthesis revealed more cases, where Actinomyces species caused prosthetic joint infection [ 19 ]. Drug resistance is not considered a problem in actinomycosis, therefore penicillin G or amoxicillin are considered first-line drugs for the treatment of actinomycosis together with surgical debridement of abscesses [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of antibiotics into the lesion may be delayed by weak vessels and solid capsules. Surgical interventions such as bone necrosis removal are performed for subacute or chronic voluminous lesions [ 129 ]. The recent treatments for Actinomycosis are summarized in Table 3 .…”
Section: Actinomycesmentioning
confidence: 99%
“…Ein vorzeitiger Therapieabbruch sollte daher vermieden werden. Balbinot et al sehen im Debridement nekrotischen Gewebes den Vorteil der besseren lokalen Immunantwort auf die Bakterien selbst mit letztlich verkürzter antibiotischer Folgetherapie [23]. Chronische, ausgedehnte bzw.…”
Section: Therapie Und Prognoseunclassified
“…komplizierte Prozesse (z. B. Osteomyelitis) oder Patienten mit HIV-Infektion können in seltenen Fällen eine antibiotische Therapie von bis zu 12 Monaten erfordern [1,9,[22][23][24]. In den Fällen 4 und 5 waren solche Empfehlungen zur Langzeitantibiotikatherapie aufgrund der Knochenbeteiligung ausgesprochen worden.…”
Section: Therapie Und Prognoseunclassified